Using Hands-on Experiences including Various Forms of ARTS to Increase Ninth-Grade Female Students’ Interest in STEM – Final Results (Global Journal of Human-Social Science, 2023)
Due to the ever-growing number of employment opportunities in the science technology engineering and math fields increasing emphasis is placed on STEM education at all levels This paper reports on research focused on increasing STEM interest and awareness in ninth- grade minority female students primarily from a low socioeconomic background Thirty-seven female students participated in this research study They attended fifteen hour-long sessions of STEM-infused hands-on workshops presented by university professors in the College of Education and the College of Arts and Sciences The workshops took place during school hours adding to their regular curriculum The school does not currently have an arts program although the founder of the school is a music artist Therefore the workshops incorporated the arts as the central theme while the lessons were delivered in biology chemistry engineering and mathematics The study is motivated by the need to close the achievement gap and improve the representation of women and minorities in STEM fields Data were collected through surveys assessments and interviews and analyzed using quantitative and qualitative methods The significance of the study lies in the potential to inspire underserved females to enter the STEM fields
Keywords: high school STEM education; female students; integrating the ARTS; STEM interest; and awareness